PERENCANAAN MASTER PLAN SI/TI MENGGUNAKAN METODE WARD AND PEPPARD (STUDI KASUS KAMPUS ALFA PRIMA) - I Gede Agus Ditha Praptika Putra; I Putu Agus Swastika; I Gede Juliana Eka Putra (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
This study discusses building an information technology master plan at Alfa Prima Campus . The purpose of this research is of course required the support of reliable information technology and information systems. In ensuring that the use of IS / IT can support the Alfa Prima Campus, an IS / IT master plan is needed in the form of a document, which is called an IT master plan. There are several methods used to create this information technology master plan, namely the ward and peppard method. The ward and peppard method consists of an input stage and an output stage. The input stage consists of an internal business environment analysis, an external environment analysis, an internal IS / IT analysis and an IS / IT analysis for the internal environment. In addition, the use of this method uses Value Chain analysis, SWOT analysis, Mc. analysis. Farlan Grid. The results of this study are the results of the output stage which consists of IT staretgi. From the results of this stage, it is hoped that the Alfa Prima Campus can apply this information technology in accordance with the implementation plan.